SATUAN MORFOLOGI DASAR LAUT PERAIRAN SELATAN PULAU LAUT, KALIMANTAN SELATAN, SEBAGAI PRODUK AKTIVITAS STRUKTUR GEOLOGI BAWAH PERMUKAAN - Aryanto, NCD; Surachman, M (Pusat Survei Geologi, 2008)
The studied area is located in south Kalimantan waters. Regionaly and physiographically it is an interesting location because this location is the transition area between the west and east Indonesian regions in which their geologic setting are very different.The transition area is reflected by the difference in the sea floor morphology. The bathymetry contour pattern at the western area that is part of the Sunda Shelf is reflected by a straight contour and distanlyspaced among them. Its slope is not more than 1” which is then calledas a Plain morphology unit. While the eastern area has a locally close pattern and its slope Is quitegentle. This feature is called as a Reef hilly morphology unit. Keywords: sea floor morphology unit, subsurface structure, Kalimantan